Analisis Semantik Kata Serapan Bahasa Arab-Melayu Dalam Kitab Sifat Dua Puluh - Rahman, Aulia; Aulia Rahman; Bahruddin, Uril (Institut Agama Islam Negeri Metro, 2024)
This study aims to analyze the absorption words in Malay Arabic in the book of nature twenty through a semantic approach. The research method used is qualitative research with an exploratory descriptive model with the object of research, namely Malay Arabic writing in the book of twenty nature by Sayyid Uthman. The data was obtained from the exploration of the book and other related literature sources, then the data was analyzed using a semantic approach by classifying the types of words absorbed by the types of adoption, adaptation, translation and creation. This research found that in the book of nature twenty there are words of absorption of the types of adoption, adaptation, translation and creation. The word absorption of the adoption type has the same form of writing and pronunciation in Malay Arabic writing. The type of adaptation has a different form of writing and pronunciation in Malay Arabic writing. This is given that not all Arabic letters have vowels. Then the word absorption of the translation type has a conceptual unity between Arabic and Malay Arabic. Furthermore, the type of creation has a different form of pronunciation after being lent to the Arabic Malay script and does not have a unity of concept that the researcher divides into two forms, namely the type of ordinary word creation and the type of word creation that resembles Arabic words/sentences.